Polyethylene glycol assisted synthesis of pristine vanadium tetrasulfide nanostructures as high performance electrode material for symmetric supercapacitors. (July 2022) - Rajendran, Kumuthini; Rajendran, Ramachandran; Anthuvan, Allen Joseph; Nagamony, Ponpandian; Therese, Helen Annal
Abstract: Partonite (VS4 ) - based nanostructures have recently received significant attention in electrochemical energy storage due to the intriguing physico-chemical properties emerging from their unusual crystallographic structure. Besides, the morphology, surface area, porosity, and pore size all play a crucial role in attaining a high-performance energy storage device, particularly in supercapacitors. Herein, the pristine VS4 nanostructures with various morphologies are synthesized through a simple hydrothermal method with the aid of PEG. The influence of PEG on the morphology, physicochemical properties, and electrochemical performance is discussed. Among all of these, the VS4 electrode labeled as PEG 55 exhibits a high specific capacitance of 1675 F/g at 0.5 A/g in 1 M Na2 SO4 . The electrode delivers a good cycling performance with the capacity retention of 90% up to 5000 cycles. Moreover, the VS4 symmetric supercapacitor (SSC) device delivers a high energy density of 94 Wh/kg and power density of 400 W/kg with excellent cycling stability (83.5% up to 10, 000 cycles). The results demonstrate that the VS4 nanostructure could be a promising candidate for supercapacitor applications. Graphical abstract: Unlabelled Image Highlights: 1D quasi-layered VS4 nanostructures of various morphology were synthesized. VS4 nanostructures exhibit superior electrochemical performance. A high specific capacitance of 1657 F/g was observed. Symmetric SCs showed an excellent performance (C-1055 F/g, E-94 Wh/kg, P-400 W/Kg). Device posses a good capacitive retention of 86% up to 5000 cycles.